Explore the Impact of Marine Plastic Pollution and Countermeasures - Chen Xiaobei (MATEC Web of Conferences)
This paper aims to examine the scope of marine plastic pollution, its effects on the environment, and its socioeconomic effects on human society. The sources, distribution, and effects of plastic litter in marine ecosystems are examined in this study, which also emphasizes the growing threat that plastic litter poses to marine life and coastal economies by analyzing the most recent data available. Current efforts to address the issue are still insufficient, even after the implementation of numerous solutions, including international agreements and waste management projects. The findings suggest that while some of the measures show little promise, a global approach is essential to effectively tackle the problem.